An act of love eaudiobook - Thayer, Nancy (Recorded Books Inc., 1997)
Reminiscent of Judith Guest's Ordinary People, this novel is a deeply moving portrait of a family torn apart by a search for truth. Deftly capturing both the comfort and security of family bonds and the pain when these bonds are assaulted, Nancy Thayer has created a powerful domestic drama. The McFarland's marriage is a success: they rejoice in their seven years together and in the friendship that has developed between Emily and Bruce, teenaged children from each of their first marriages. But when Emily attempts suicide at her boarding school, it is only the first indication of a dangerous compulsion simmering beneath the calm surface of the McFarland household. From its stark opening scene in a hospital emergency room to the final hopeful evening, An Act of Love will hold you in its spell. Narrator Barbara Caruso adds both warmth and emotional tension to a story that challenges conventional notions of punishment and forgiveness.